The Influence of Lowness of Ufuk in Reckoning of Maghrib Prayer Times at City’s Grand Mosque in Indonesia - Masruhan Masruhan (Al-Mizan (e-Journal), 2018)
The treasure of the reckoning time of Maghrib prayer in the study of astronomy has a variety of criteria in determining the height of the Sun, namely: rounding the number -1° and the formulation of the Sun's height: - (horizon + semidiameter + refraction low). This study discusses the implementation of these two criteria into the reckoning time of prayer at the city/regency Grand Mosque. This research is library research, using quantitative descriptive analysis. This results showed namely: the results of testing the accuracy of the reckoning of the criteria prayer time ho = -1 ° slower in Maghrib time if the input height is below 33 masl. Then the results of the reckoning prayer time criteria ho = -1 ° have the results of the Maghrib time which is the same as the reckoning criteria ho = - (ku + ref + sd) when the input height is 33 masl. And the results of the reckoning time criteria ho = -1 ° faster at Maghrib time which is above 33 masl. While the tolerance limit of a difference of 1 minute is reaching an altitude of 201 masl means that a total of 82.14971% of the total Grand Mosque of the City is still safe. In Indonesia, the height of the Great Mosque of the City above 201 masl or the difference of more than 1 minute is 17,850287%, which means that it is still not safe to use the initial reckoning when the criteria are ho = -1° and it is necessary to add corrections to horizon modesty (place height).